2021
DOI: 10.1371/journal.pone.0248433
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular changes on optical coherence tomography angiography after rhegmatogenous retinal detachment vitrectomy with silicone tamponade

Abstract: Purpose We aimed to evaluate microvascular changes on optical coherence tomography angiography (OCTA) in patients with rhegmatogenous retinal detachment (RRD) who underwent silicone oil (SO) tamponade and compare changes according to macular involvement. Methods This retrospective study included 48 patients with unilateral RRD who underwent vitrectomy and SO tamponade and were stable after SO removal. Control data were obtained from the fellow healthy eye. Ophthalmic examinations, including best corrective v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Fang et al compared air and silicone oil endotamponade, and observed decrease of VD in both groups [22]. Lee and coauthors reported VD decrease after successful silicone oil removal [23].…”
Section: Plos Onementioning
confidence: 99%
“…Fang et al compared air and silicone oil endotamponade, and observed decrease of VD in both groups [22]. Lee and coauthors reported VD decrease after successful silicone oil removal [23].…”
Section: Plos Onementioning
confidence: 99%
“…Silicone oil tamponade may be associated with decreased macular vessels density, both in SO-filled eye and after ROSO ( Table 4 ). This may affect the superficial capillary plexus (SCP) alone [ 156 , 159 ] or the deep capillary plexus (DCP) alone [ 160 , 161 ], whereas the involvement of both plexuses has been less commonly reported [ 160 ]. On the one hand, it has been hypothesized that the SCP and the superficial retinal layers, being in contact with SO, could be more susceptible to potential SO-related mechanical/cytotoxic damage [ 159 ]; on the other hand, the DCP is considered more susceptible to ischemic damage due to its intraretinal location [ 162 ].…”
Section: Retinal Changes Associated With Silicone Oilmentioning
confidence: 99%
“…This may affect the superficial capillary plexus (SCP) alone [ 156 , 159 ] or the deep capillary plexus (DCP) alone [ 160 , 161 ], whereas the involvement of both plexuses has been less commonly reported [ 160 ]. On the one hand, it has been hypothesized that the SCP and the superficial retinal layers, being in contact with SO, could be more susceptible to potential SO-related mechanical/cytotoxic damage [ 159 ]; on the other hand, the DCP is considered more susceptible to ischemic damage due to its intraretinal location [ 162 ]. In addition, Liu et al [ 163 ] speculated that the superficial vascular changes might also be related to the elevation of IOP as they found a decreased parafoveal SCP VD only in eyes that had experienced raised IOP during the follow-up.…”
Section: Retinal Changes Associated With Silicone Oilmentioning
confidence: 99%
See 2 more Smart Citations